(1114) Human Settlements and Health - A Comprehensive Paper of World Health Organization for Habitat The United Nations Conference on Human Settlements - N. A. Hassouna (معهد التخطيط القومى, 2026)
The complexity of the topic health and human settlements is such that in order to consider the various interactions and implications involved it is necessary to construct a central theme around which the various different approaches to solving many of the related problems can be brought together in an integrated, comprehensive way. One of the more focal issues around which health problems have been observed to revolve is the imbalance that exists or which often develops, between population and the organizational, technological, human and monetary resources that are involved in improving the quality of life of that population. It is through these two fundamental forces that help shape the nature of human settlements that this paper will consider the problem of health and habitat.